ANALISIS POLA ASUH TERHADAP KEMANDIRIAN PESERTA DIDIK KELAS 5 SD SIVALIPUTTA KUBURAYA - Dharma, Galih Eka (STKIP Persada Khatulistiwa Sintang, 2025)
Independence is a crucial aspect of a child's development, influenced by parenting styles. This study focuses on analyzing the impact of democratic, authoritarian, and permissive parenting styles on the independence of fifth-grade students at SD Sivaliputta, Kuburaya. The research uses a qualitative approach with a case study design to explore the experiences and perceptions of students, parents, and teachers. The findings indicate that the democratic parenting style is the most effective in supporting children's independence, while authoritarian and permissive styles tend to hinder the development of independence. These findings provide insights for parents and educators in shaping strategies that support the development of student independence through appropriate parenting styles.